2018
DOI: 10.1101/270694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why do eukaryotic proteins contain more intrinsically disordered regions?

Abstract: Intrinsic disorder is much more abundant in eukaryotic than in prokaryotic proteins. However, the reason behind this is unclear. It has been proposed that the disordered regions are functionally important for regulation in eukaryotes, but it has also been proposed that the difference is a result of lower selective pressure in eukaryotes. Almost all studies intrinsic disorder is predicted from the amino acid sequence of a protein. Therefore, there should exist an underlying difference in the amino acid distribu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…However, it is still unclear what the cause of this adjustment is, be it selection for certain nucleotide sequence properties such as GC content or codon usage bias. Recent studies have identified differing GC (Basile et al 2017 ) and amino acid content (Basile et al 2019 ) as causes of differences in disorder content of eukaryotic proteins.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is still unclear what the cause of this adjustment is, be it selection for certain nucleotide sequence properties such as GC content or codon usage bias. Recent studies have identified differing GC (Basile et al 2017 ) and amino acid content (Basile et al 2019 ) as causes of differences in disorder content of eukaryotic proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The average predicted disorder across all assessed mucins (58%) far exceeds the average of what is present throughout the human (30%) and eukaryotic (32%) proteomes. [25][26][27]72 In fact, this would place the mucin family in the top 10-15% most disordered proteins found in the human Ensemble database analyzed by D 2 P 225 with the majority of individual mucins harboring a far greater amount of disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In young animal pfams, the two amino acids that are most enriched are serine and proline. These are two of the amino acids previously identified as most responsible for differences between eukaryotes and prokaryotes via the greater quantity of 'linker' regions (protein sequences between pfams) of eukaryotic proteins (Basile et al 2019). This suggests that the signal in eukaryotic linkers reflects an animal-specific trend across all recent protein-coding sequences, both when they are annotated as domains and when they are not.…”
Section: Trends In Amino Acid Compositionmentioning
confidence: 99%